DISCOVERING EFL LEARNERS PREFERENCES TOWARD PRONUNCIATION PRACTICE CLASS - Rosyid, Abdul; Sofyan, Deddy (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
This following study is an effort to discover students preferences toward pronunciation practice class. The method used was survey method. The sample of this research was the second semester students of English Education Study Program, Faculty of Teacher Training and Educational Sciences, Pakuan University. The data was gathered through questionnaire administered online. Having analyzed the questionnaire, there are three important findings. The first one dealing with students opinion related to the materials given in pronunciation classroom. It was discovered that almost all of the students are in the positive side dealing with the issue. The pronunciation materials that the students agree to be maintained are focusing on segmental and suprasegmental of pronunciation. The second findings related to the students opinion about pronunciation teaching and learning process. It was found out that the students prefer to learn pronunciation material through real practice activities; such as reading aloud, listening English songs, watching English videos and interacting with native speakers. The final point addressed students preferences toward pronunciation materials. The materials that have been discussed so far are the materials that they like and meet their need. The materials are related with vowels, consonants, diphthongs, lingking sounds, intonation, and stress. There is also interesting finding related to the materials that the students want to learn. English around the world, pronuncing English slang and online application for learning pronunciation are three novel materials that students want to study